Reduced aerosols and intensified summertime rainfall in India during the pandemic suggest potentially more amplified precipitation in the future - Fan Wang; Meng Gao (Environmental Research Letters)
Aerosol pollution is anticipated to decrease in the future, yet the associated effects of reduced aerosol loading on precipitation remain insufficiently explored. Widespread reductions in anthropogenic emission during COVID-19 lockdowns offer a unique opportunity to understand precipitation responses to changes in anthropogenic aerosols. Based on observations and regional and global climate-chemistry coupled model simulations, we attribute unprecedented precipitation in India during the 2021 lockdown to decreased aerosol levels due to emission reductions. Reduced aerosol loading leads to a northward shift of the subtropical westerly jet, which induces a westward movement of the subtropical southern branch trough and negative sea-level pressure anomalies over the eastern Arabian Sea. This shift facilitates water vapor transport from surrounding oceans to land, increasing precipitation in India by approximately 24.2% in May according to the Weather Research and Forecasting model coupled with chemistry simulations and by 28.5% over the entire lockdown period according to the Community Earth System Model version 2.1.3 simulations. Future projections under the lower aerosol emission scenario indicate an additional enhancement in monsoon precipitation in India. Our findings highlight the complex interplay between aerosol emissions and hydrometeorological dynamics, with implications for understanding future precipitation changes and providing theoretical reference for water resource management.